2022
DOI: 10.1186/s12913-022-07809-6
|View full text |Cite
|
Sign up to set email alerts
|

Medical documentation practice and associated factors among health workers at private hospitals in the Amhara region, Ethiopia 2021

Abstract: Introduction Medical documentation is an important part of the medical process as it is an essential way of communication within the health care system. However, medical documentation practice in the private sector is not well studied in Ethiopian context. The aim of this study was to assess the practice of medical documentation and its associated factors among health workers at private hospitals in the Amhara region, Ethiopia. Method An institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 34 publications
4
18
2
Order By: Relevance
“…Health professionals for whom standard documentation tools were available were 2.5 times more likely to document routine practices than those for whom standard documentation tools were not available. This finding is consistence with a study done in Australia,26 Tigray18 and Amhara regions 23. This might be due to familiarisation with standard documentation sheets, and the accessibility of integrated routine health information forms for recording and reporting 27…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Health professionals for whom standard documentation tools were available were 2.5 times more likely to document routine practices than those for whom standard documentation tools were not available. This finding is consistence with a study done in Australia,26 Tigray18 and Amhara regions 23. This might be due to familiarisation with standard documentation sheets, and the accessibility of integrated routine health information forms for recording and reporting 27…”
Section: Discussionsupporting
confidence: 86%
“…The study revealed that health professionals’ routine practice documentation was good (51.1%). This finding is higher than previous similar studies, which found 44.2% in Nigeria,17 33.3% in Indonesia12 and 37.4%–48.8% in different parts of Ethiopia 3 18 23. However, the finding is lower than the study done in Jamaica, which reports that health professionals’ documentation practice is 98% 24.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Ethiopian medical documentation culture is not ideal. The health workers’ attitude towards medical documentation, time constraints, inadequate knowledge and lack of training could all be contributing factors 9 10. These elements have been the main focus of the ongoing quality enhancement initiative.…”
Section: Discussionmentioning
confidence: 99%